Discovering the knowledge transfers framework on aero-composite manufacturer in Malaysia - Mohd Irman, Ibrahim; Ong, Huei Ruey; Azrul Zamir, Mohd Idris; Khan, Maksudur R.; Gomes, Martin
This work elucidated the knowledge transfer method used by an international first tier advanced composite multinational company supplier in transferring the technical knowledge to a Malaysian advanced composite manufacturer. Effective route of knowledge transfer could significantly improve the performance of the company. The process of the transferring knowledge is an ongoing progression of learning, adjusting, and improving. An excellent knowledge transfer could benefit both the knowledge provider and receiver. A “Backward Engineering” investigation on the relationship between the factors during the knowledge transfer process is useful, to be an ideal reference for others. This paper exhibits the technological transfer executed by the aero-composite manufacturer. Method chosen in this study is focus group discussion involving the working committee of respective programme. It was found that a systematic two stages with multi-phases of knowledge transfer has been explored during flat-curvature structures aero-composite project. Tacit and explicit knowledge is important for transferring technical knowledge in industry context. It is noticed that a useful knowledge transfer mechanism has an impact on the performance of organization such as increases in productivity, profits, and growth.